Analisis Mutu Layanan Perawat pada Rumah Sakit Ken Saras, Bergas - David Nakka Gasong; Dennys Christovel Dese; Frisky Kaluasa (Jurnal Keperawatan Muhammadiyah, 2022)
Background: The quality of nursing services is one of the factors in determining the quality of health services and is a determinant of the representation of health service institutions in the community. Ken Saras Hospital is one of the private hospitals in Bergas which provides comprehensive advanced referral individual health services. The COVID-19 pandemic is one of the challenges in providing the best nursing services for patients. This research was conducted with the aim of knowing the quality of nurse services in accordance with patient expectations of nursing services provided by Ken Saras Hospital. Method This research is descriptive analytic with the type of observational research using survey methods. The technique for taking the number of respondents will be determined based on the Slovin formula. Discussion: The results showed that the service quality of nurses based on 5 aspects of the assessment was very good. This can be seen from the patient's answers stating that the quality of nurse services is good in indicators, tangible/physical evidence (94.4%), reliability (100%), empathy/caring (98.8%), responsiveness/responsiveness (100%), and assurance (96.1%). Conclusion Based on the results of this study, the quality of service provided by nurses at Ken Saras Hospital in these 5 aspects indicates that the quality of service provided by nurses at Ken Saras Hospital is good and satisfactory.